2008
DOI: 10.1038/mp.2008.5
|View full text |Cite
|
Sign up to set email alerts
|

Are some cases of psychosis caused by microbial agents? A review of the evidence

Abstract: The infectious theory of psychosis, prominent early in the twentieth century, has recently received renewed scientific support. Evidence has accumulated that schizophrenia and bipolar disorder are complex diseases in which many predisposing genes interact with one or more environmental agents to cause symptoms. The protozoan Toxoplasma gondii and cytomegalovirus are discussed as examples of infectious agents that have been linked to schizophrenia and in which genes and infectious agents interact. Such infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
195
0
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(207 citation statements)
references
References 80 publications
5
195
0
7
Order By: Relevance
“…As a first step, the prevalence of antibodies against T. gondii could be determined in patients with IBD compared to well-selected control populations; a slightly but significantly higher seropositivity rate (based on Sabin-Feldman dye test results) has been observed previously in a small cohort of Crohn's patients over the age of 40 in Israel (Rattan et al 1986). Results of studies that include larger patient numbers should be especially interesting since an association of T. gondii infection (based on the presence of IgG antibodies) with psychiatric disorders has been suggested (Yolken & Torrey 2008). …”
Section: Resultsmentioning
confidence: 99%
“…As a first step, the prevalence of antibodies against T. gondii could be determined in patients with IBD compared to well-selected control populations; a slightly but significantly higher seropositivity rate (based on Sabin-Feldman dye test results) has been observed previously in a small cohort of Crohn's patients over the age of 40 in Israel (Rattan et al 1986). Results of studies that include larger patient numbers should be especially interesting since an association of T. gondii infection (based on the presence of IgG antibodies) with psychiatric disorders has been suggested (Yolken & Torrey 2008). …”
Section: Resultsmentioning
confidence: 99%
“…Epidemiological studies have shown that infections and autoimmune diseases are clin ic ally important risk factors for the development of schizo phrenia. [1][2][3] Furthermore, a recent study integrating results from a meta analysis of genome wide association studies in schizophrenia found that the most significant changes were observed in genetic loci related to the immune system. 4 Also, patients with schizophrenia show microglial activation, as re vealed by positron emission tomography.…”
Section: Introductionmentioning
confidence: 99%
“…This causal interface most likely occurs during prenatal or early postnatal brain development when neurons are migrating and synapses are being formed and pruned. Abundant and converging evidence from both genetic and environmental studies points to immune system aberrations as contributing a substantial risk for development of the disorder [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%